Genotypic and environmental effect on male flower production in Cupressus sempervirens clones and selection of genotypes with reduced pollen emission - Danti, Roberto; Barberini, Sara; Di Lonardo, Vincenzo; Della Rocca, Gianni (Frontiers in Plant Science, 2022)
Common cypress (Cupressus sempervirens L.) is widespread in the Mediterranean area and is frequently planted as ornamental tree in parks and gardens. Like other species of Cupressus, common cypress releases a significant amount of the total annual airborne pollen in most regions and is known as responsible for winter pollinosis. Although variation in the production and release of pollen has been observed among C. sempervirens trees growing in urban areas, no information is available on effects due to genotype × environment interaction on this trait. In this study more than 150 C. sempervirens clones were analyzed for two to four consecutive years in clonal orchards situated in central Italy to evaluate variations in the production of male cones. Variance component ANOVA underscored an important genetic control of male flowering, with high repeatability (from 0.80 to 0.95) found in single environments. Analysis for combined sites or years (in a single site) showed significant effect of environment and genotype × environment interaction on the total variance. Intra-trait genetic correlations between environments were moderate to high (from 0.40 to 0.92), which indicates that male cone production of clones is fairly consistent across years and sites. Of the 10 clones characterized by the lowest mean male cone production, three showed good stability across environments based on the linear regression coefficient and Wricke’s ecovalence. The mean cone production of these 10 clones was 5 to 10 times lower than the mean production observed in the same environment. These clones have both ornamental and hypoallergenic traits and hold promise for designing green spaces with low allergy impact.